Effect of Superficial Velocity of Pressure Difference on The Separation of Oil And Water by Using The T-Pipe Junction - Kms. Ridhuanand; . Indarto (Bandar Lampung University (UBL), 2013)
Many ways that is done to separate a mixture such as kerosene-water, such as by using branching pipes (T junction), the construction of the pipeline is composed of one side of the inlet, the run up (straight) and sidearm (upwards). This research aims to determine the effect of superficial velocity of mixture flow pressure difference at the T-junction that occurs on a kerosene-water separation efficiency. Research conducted by using a test section of the T-Junction with a 30 ° slope angle and radius bend 25 mm. pipe Material with a diameter of 1.5 inch Fleksiglass. Media used kerosene and water. The variables measured, namely that of kerosene and discharge water out through the side arm and run arm based on superficial velocity of kerosene and water according the test matrices. The difference in pressure at the T-Junction. Overall results of nicest phase separation occurs at 58% water cut, Jmix = 0.36 m/s downstream flow barriers, with 40% in 550,7 Pa pressure resulted in Fk = Fw = 97% and 2% that flows to the side arm, and Fk = Fw = 3% and 98% of that flows to run arm. The smaller the value of water cut the better efficiency of separation is achieved. The increasing speed of the shear stress of kerosene and superficial result in increasing pressure fluctuations.Also increased pressure downstream barriers. On Jmix 0.36 m/s is highest pressure 1400 Pa, on PSD signal fluctuations of 8000. With the increasing speed of superficial kerosene PSD magnitude decreased, and the strength of the apex of the PSD increased. On a superficial water medium speed with increasing speed of superficial water and kerosene for constant pressure difference loss occurring on the area of the inlet and run T-junction